A Distinct Class of Chromoanagenesis Events Characterized by Focal Copy Number Gains. Issue 7 (6th April 2016) - Masset, Heleen; Hestand, Matthew S.; Van Esch, Hilde; Kleinfinger, Pascale; Plaisancié, Julie; Afenjar, Alexandra; Molignier, Romain; Schluth‐Bolard, Caroline; Sanlaville, Damien; Vermeesch, Joris R.
Abstract : Here we present three patients with developmental anomalies carrying a single chromosome with 8 to 11 large copy number gains, but no large deletions. FISH and DNA sequencing revealed these duplicons do not match the characteristics of typical previously reported chromothripsis‐like chromosomes, suggesting an alternative mechanistic origin. ABSTRACT: Chromoanagenesis is the process by which a single catastrophic event creates complex rearrangements confined to a single or a few chromosomes. It is usually characterized by the presence of multiple deletions and/or duplications, as well as by copy neutral rearrangements. In contrast, an array CGH screen of patients with developmental anomalies revealed three patients in which a single chromosome carries from 8 to 11 large copy number gains confined to a single chromosome or chromosomal arm, but the absence of deletions. Subsequent fluorescence in situ hybiridization and massive parallel sequencing revealed the duplicons to be clustered together in distinct locations across the altered chromosomes. Breakpoint junction sequences showed both microhomology and non‐templated insertions of up to 40 bp. Hence, these patients each demonstrate a single altered chromosome of clustered insertional duplications, no deletions, and breakpoint junction sequences showing microhomology and/or non‐templated insertions. These observations are difficult to reconcile with current mechanistic descriptions of chromothripsis and chromoanasynthesis. Therefore, we hypothesize those rearrangements to be of a mechanistically different origin. In addition, we suggest that large untemplated insertional sequences observed at breakpoints are driven by a non‐canonical non‐homologous end joining mechanism.